2018
DOI: 10.5194/nhess-18-1703-2018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and validation of the PTVA tsunami building vulnerability model using the 2015 Chile post-tsunami damage data in Coquimbo and La Serena cities

Abstract: Abstract. Chile is highly exposed to tsunami hazard from large earthquakes often occurring along the Peru–Chile trench, like the 16 September 2015 event. However, only recently has tsunami hazard been considered in the land-use policies of the Chilean coast. These new regulations must enforce the identification of the most vulnerable sectors of the Chilean coastal cities. This paper analyses and validates the two latest versions of the Papathoma Tsunami Vulnerability Assessment (PTVA) model in the 2015 tsunami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The purpose of classifying buildings into these groups as mentioned above is to categorize buildings based on their construction strength. According to available post flood field surveys [39][40][41], lightweight material and wood-constructed buildings have always suffered more serious structural damage. Masonry-constructed buildings are considered to have a moderate vulnerability to flooding, while reinforced concrete structures and steel/IBS structures are considered to be highly resistant to flood hazard.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of classifying buildings into these groups as mentioned above is to categorize buildings based on their construction strength. According to available post flood field surveys [39][40][41], lightweight material and wood-constructed buildings have always suffered more serious structural damage. Masonry-constructed buildings are considered to have a moderate vulnerability to flooding, while reinforced concrete structures and steel/IBS structures are considered to be highly resistant to flood hazard.…”
Section: Discussionmentioning
confidence: 99%
“…The Indian Ocean tsunami in 2004 (Athukorala and Resosudarmo 2005), the 2010 Chilean tsunami (Fritz et al 2011;Khew et al 2015), the Great East Japan earthquake and tsunami in 2011 (Suppasri et al 2012;Davis et al 2012); Hurricanes Katrina (Brunkard et al 2008) and Sandy (Seil et al 2016); and Typhoon Haiyan (Mikami et al 2016) have all caused devastating loss of life and economic damage. Many postevent field surveys have shown that, in addition to failures from surge and wave loading (Lynett et al 2003;Fritz et al 2011;Fraser et al 2013;Tomiczek et al 2017;Izquierdo et al 2018), significant damage has been associated with waterborne debris impacts. Waterborne debris includes a wide variety of objects carried inland by the flow, for example, structural fragments, such as concrete blocks and wooden poles (Hatzikyriakou et al 2016), shipping containers (Mikami et al 2016), boats and cars (Ghobarah et al 2006), boulders (Fritz et al 2011;Kennedy et al 2017), and propane tanks (Stolle et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Fragility functions derived from a single tsunami event means they will be characteristic of local asset and event characteristics. For transportation assets, only bridge structures have been analysed for fragility function development (Kawashima and Buckle, 2013;Koks et al, 2019;Shoji and Moriyama, 2007). These studies applied tsunami inundation depth as the hazard intensity measure (HIM), as it usually has a strong correlation with impact and is relatively easy both to model and to measure post-disaster.…”
Section: Introductionmentioning
confidence: 99%
“…Although post-event tsunami surveys commonly record road impacts as physical damage levels, levels of service can also be considered, which include but are not limited to physical damage. Coastal road networks are most commonly damaged or totally destroyed, either by debris impact or erosion of the substrate material (Eguchi et al, 2013;Horspool and Fraser, 2016;Kawashima and Buckle, 2013;Kazama and Noda, 2012;MLIT, 2012), and have reduced levels of service due to debris litter (Evans and McGhie, 2011). Debris litter is a widely identified post-event impact that affects the functionality of an otherwise undamaged road.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation